(untitled) (Physical Education, Health and Social Sciences, 2025)
This article explores the intricate relationship between Pakistani society and globalization as they occur in the novel How to Get Filthy Rich in Rising Asia 2013 by Mohsin Hamid. This research is analysed with the help of Arjun Appadurai’s theory of globalization, based on the juncture of scapes: Ethnoscape, Technoscape, Financescape, Mediascape, and Ideoscape. Hamid’s novel is the story of a nameless hero who migrates from rural to urban for the sake of better economic struggle. Furthermore, this paper presents the analysis of the scapes in the narrative as a method of noticing how each scape is present and how it portrays a sense of an ever-changing cultural identity in the setting of a South Asian context and a liberal order. The experimental nature of the novel, second-person point of view, and satirical tone give plenty of space to utilize the theoretical model proposed by Appadurai. Arjun Appadurai develops a framework that is useful in the analysis of literary text, How to Get Filthy Rich in Rising Asia 2013. Thus, the article comes to an academic conclusion by analyzing the effectiveness of the framework and proposing new ways of looking at globalization in Pakistani literature.